Phytochemical screening of identification of some compounds from Paal Patpam - Sathiyaseelan, V.; Keerthiga, S.; Harishanth, N.; Velauthamurthy, K. (Unit of Siddha Medicine, University of Jaffna, 2018)
Siddha Medicine is an ancient system of Medicine, which is largely therapeutic in nature has a rich heritage and history. Siddha Medicine is practiced among the Tamil speaking people. The Medicine in Siddha system is prepared from raw material of herbs, metals, minerals and animal products. Paal patpam is one of the Siddha drug chosen from the Anupoga vaithya navaneetham. Based on the text paal patpam is suggested to udatsoodu, enpusoodu, vellai. This drug contains cow milk and root of Abutilon indicum used to prepared it. Aim of this study is screening of identification of some compounds of paal patpam. Paal patpam is prepared and the sample was analyzed at the department of chemistry, University of Jaffna, Sri Lanka for the standard phytochemical screening and qualitative identification of amine, carboxylic acid, phenol, alcohol, ketone, aldehyde, esters, ammonium, amide, sulfur, nitrogen, phosphorus, halogens ionic sulfur, ionic halogens and ionic phosphorus. By the qualitative analysis, indicated that the amine, carboxylic acid, amide, nitrogen, phosphorus and ionic phosphorus were found in the sample. The present of above mention chemical compounds in paal patpam may increase the immunity of the body and have not any side effects.
Keywords: Paal patpam; Phyto chemical screening; immunity